The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.5762/kais.2016.17.9.619
|View full text |Cite
|
Sign up to set email alerts
|

The Metacognition, Self-efficacy and Self-leadership among Nursing Students

Abstract: This study was conducted to identify the relationship between metacognition, self-efficacy and self-leadership among nursing students, and to investigate the factors influencing self-leadership. The subjects of this study consisted of 445 nursing students of S university in S city. Data were collected using self-reported questionnaires from May 23 to June 10 and analyzed based on frequencies, t-tests, ANOVA, Scheffe's test, Pearson's correlation, and multiple regression, which were conducted using the IBM SPSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Han & Kwon (2016) showed a significant and positive relation among this leadership and self-efficacy. Different studies about the subject also showed that there were significant positive relationships among self-efficacy and self-leadership (Lee, 2015;Lee & Kim, 2016;Lee, Park, & Kim, 2014;Wang, Jung, Park, Yoo, Bae, & Kim, 2016). According to these results, if students had had self-leadership behaviours, their self-efficacy may have increased.…”
Section: Discussion Conclusion Recommendationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Han & Kwon (2016) showed a significant and positive relation among this leadership and self-efficacy. Different studies about the subject also showed that there were significant positive relationships among self-efficacy and self-leadership (Lee, 2015;Lee & Kim, 2016;Lee, Park, & Kim, 2014;Wang, Jung, Park, Yoo, Bae, & Kim, 2016). According to these results, if students had had self-leadership behaviours, their self-efficacy may have increased.…”
Section: Discussion Conclusion Recommendationsmentioning
confidence: 91%
“…Another study explains significant and positive relation among self-leadership and efficacy (Norris, 2008). Similarly, some studies reveal indirect and direct relation among self-efficacy and selfleadership in many contexts (Han & Kwon, 2016;Lee, 2015;Lee & Kim, 2016;Lee, Park & Kim, 2014;Unsworth & Mason, 2012;Wang, Jung, Park, Yoo, Bae & Kim, 2016).…”
Section: Self-leadershipmentioning
confidence: 93%
“…셀프리더십은 문헌에서 간호대학생의 감성지능 (Kim, 2018), 자기효능감, 사회적 지지 (Lee, Lee, & Kim, 2019), 간호전문직관 (Park, 2015), 전문직 자아개념 (Dong & Choi, 2016), 메타인지, 전공만족과 관련이 있으며 (Wang et al, 2016), 문제해결능력, 비 판적 사고성향 (Kim, 2017), 임상수행능력 (Dong & Choi, 2016), 학업성취도에 영향을 미치는 요인으로 나타났다 (Kim, 2018). 그 리고 셀프리더십은 다양한 관련변인에 의해 영향을 주고받으며 학년이 진급됨에 따라 향상되는 것으로 (Kum, Seo, Kim, Han, & Kim, 2019;Park, Yoo, Seo, & Park, 2015) 훈련을 통해 학습이 될 수 있는 능력이므로 간호대학생의 셀프리더십이 개발될 수 있도록 체계적인 전략과 노력이 필요하다 (Won & Cho, 2013 (Won & Cho, 2013) 과 메타분석 연구 (Yu, Park, & Jang, 2018) (Borenstein, Hedges, Higgins & Rothstein, 2009;Shin, 2017 (Rosenthal, 1984).…”
unclassified